Evolution of Cloud Computing Research in Information Systems - Loso Judijanto; Arnes Yuli Vandika; M. Ammar Muhtadi (West Science Information System and Technology, 2024)
Cloud computing has become a cornerstone of modern information systems, driving significant advancements across various industries. This study conducts a bibliometric analysis to explore the evolution of cloud computing research within the field of information systems, focusing on key trends, influential publications, and author collaborations. The analysis, based on data from Google Scholar, reveals that security has consistently been a critical area of focus, reflecting the ongoing concern for safeguarding cloud environments. Additionally, the integration of cloud computing with emerging technologies like the Internet of Things (IoT) and big data is highlighted as a growing trend, emphasizing the expanding applications of cloud computing. The study also identifies distinct research clusters, suggesting opportunities for enhanced collaboration across different subfields. While the findings offer valuable insights for both researchers and practitioners, the study acknowledges its limitations, including the reliance on a single database and the potential oversimplification of complex research interactions. Future research should consider these limitations and explore new avenues to further understand and enhance cloud computing practices.